HESTER'S EFFORT ATTAINING LOVE IN ROLAND JOFFE'S THE SCARLET LETTER MOVIE (1995): AN EXISTENTIALIST APPROACH - SULISTYOWARNI, YUNI EKO (2010)
The research is aimed to know the Hester's effort to attain love in Roland Joffe's The Scarlet Letter movie by using existentialist approach. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the existentialist approach. The research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is The Scarlet Letter movie directed by Roland Joffe released in 1995. While the secondary data sources are other materials taken from books, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise en scene, cinematography, sound, and editing are related to each other and form the unity into good quality . Second, based on the existentialist analysis, the writer describes the result of research in which life is more meaningful if people uses it with unlimited creativity, there is also called freedom. Freedom here means the freedom of existence, like fall in love, get married, school, etc. . She is considered by society as a sinner and adulterer. Then from this, She knows that life has choice and struggle